PROGNOSIS OF BAKU ARCHIPELAGO HYDROCARBON POTENTIAL BY TYPES OF MUD VOLCANOES - Narimanov, N.; Gahramanov, G.; Babayev, M.; Shpyrko, S.; Nasibova, G.; Mukhtarova, Kh. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Mud volcanoes are indicators of the oil and gas generation processes in the hydrocarbon basins and can show the hydrocarbon potential of local anticline structures where they arise. The quantitative study of the composition of gas ejecta from volcanoes and their age can reveal the generation zones in the sedimentary cover and help assess the hydrocarbon bearing potential of an area. Mud volcanoes are often spatially related to the disjunctive faults intersections, and, on the other hand, there is a clear correlation between the location of the major oil and gas deposits and deep faults. Therefore, ejecta of mud volcanoes present a tool for geochemical probing of potentially hydrocarbon bearing structures. We used a spatial analysis of the composition of gases in mud volcanoes in order to reveal the prospective hydrocarbon targets in Baku Archipelago, located in the western part of the South Caspian Basin. The results confirm the prognosis for the existence of major gas condensate and gas accumulations in its deep water part. The calculations for the ages of mud volcanoes show that they refer to Cretaceous and Miocene-Pliocene periods.
Keywords: methane; ethane; propane; butane; pentane; carbon dioxide; nitrogen; oxygen; mud volcano; argon; helium; gas outburst; gas age; gaseous methane homologs